Amplicon sequencing identified a putative pathogen, Macrophomina phaseolina, causing wilt in African eggplant (Solanum aethiopicum) grown in Tanzania and Uganda - Xu, Xiangming; Minja, Ruth; Kizito, Elizabeth Balyejusa; Dinssa, Fekadu; Deakin, Greg; Kabod, Pamela Nahamya; Kalala, Asheri; Kweka, Eliciana; Mbwambo, Omary; Mbanzibwa, Deusdedith; Msangi, Hamza; Nakanwagi, Mildred Julian; et al. (Frontiers in Agronomy, 2024)
African eggplant (Solanum aethiopicum L.) is one of the most common traditional vegetables in Tanzania and Uganda, but its productivity is severely affected by wilt diseases caused by a number of pathogens. Plant stem and root samples were collected in several fields from many neighbouring diseased and healthy plants of the Gilo group in Tanzania and from the Shum group in Uganda to identify putative pathogens causing wilt on African eggplants. Through amplicon-sequencing of sampled diseased and healthy tissues, we identified putative causal pathogens for the wilt symptoms. Wilting of S. aethiopicum in Uganda is most likely caused by the bacterial pathogen Ralstonia solanacearum, whereas in Tanzania wilt is most likely caused by the fungal pathogen Macrophomina phaseolina, infecting roots. Infection of stems by Fusarium solani may also contribute to the wilt symptoms in Tanzania. Further artificial inoculation under controlled conditions confirmed that M. phaseolina can cause typical wilting symptoms on S. aethiopcium genotypes. The discovery of different putative causal agents of wilt in the crop demonstrates the need for site specific aetiological analysis of wilt before developing and implementing effective control methods. Further research is needed to confirm the results and develop appropriate management measures against specific wilt pathogens.